Discrete, Shallow Doping of Semiconductors via Cylinder‐Forming Block Copolymer Self‐Assembly. Issue 9 (1st May 2022) - Zhang, Yuanyi; Danielsen, Scott P. O.; Popere, Bhooshan C.; Heitsch, Andrew T.; Li, Mingqi; Trefonas, Peter; Segalman, Rachel A.; Katsumata, Reika
Abstract: Block copolymer (BCP) self‐assembly‐assisted doping for semiconductors is used to achieve discrete doping with nanometer‐scale junction depth, high throughput, and large area coverage. As devices become smaller and more sophisticated, spatial control of dopants becomes more critical. A variety of doping methods, such as monolayer doping and δ ‐doping, have been developed to replace the conventional doping method, ion‐implantation; however, lateral patterning of dopants relies on photo‐ or e‐beam lithography. To address these challenges, a self‐assembling dopant (boron)‐containing BCP is designed to directly pattern dopants on the nanometer scale. This method skips the lithography step and is compatible with directed self‐assembly approaches. The effect of the boron concentration in the BCP on the doping performance is systematically studied by changing the volume fraction of the boron‐containing block while keeping the domain spacing and the mesoscale morphology constant. Successful self‐assembly of the BCP into a hexagonally packed cylindrical morphology is confirmed by small‐angle X‐ray scattering and resonant soft X‐ray scattering with a 26 nm cylinder‐to‐cylinder distance. Doping silicon using these BCPs enables discrete doped areas with shallow (7–13 nm) junction depth as demonstrated by the depth profile of boron, and supported by a sheet resistance study. Abstract : As devices become smaller and more sophisticated, precise placement of dopants becomes more critical for miniaturization of devices. To address this challenge, polymeric spin‐on doping is developed as a hybrid of conventional inorganic spin‐on doping and recently‐developed monolayer doping. In this study, a self‐assembling dopant (boron)‐containing block copolymer is designed to directly pattern dopants on the nanometer scale.